(untitled) (Medicine Today, 2019)
Introduction: To compare and evaluate the safety and efficacy of two surgical techniques for the management of primary pterygium. Materials & Methods: The study included 176 eyes of 176 patients with primary pterygium. The mean age was 49 ± 12 years (range 24–74 years). Simple excision under local anesthesia was performed followed by closure of the bare sclera by suture less and glue free conjunctival autograft in 76 eyes of 76 patients (group 1), versus the conventional method of a sutured conjunctival autograft in 100 eyes of 100 patients (group 2). Results: The pterygium recurrence rate was 6% for group 1, 8% for group 2. Graft dehiscence occurred in 4 eyes out of 50 (8%) in group 1. Graft retraction occurred in 6 (12%) out of 50 eyes for group 1 versus 6 eyes (6%) in group 2. Pyogenic granuloma occurred in 3 (3%) eyes out of 100 in group 2. No other serious complications were noted. At the 3 week visit the overall patient satisfaction score was statistically significantly higher for group 1 (P < 0.002) compared to group 2. At 3 months postoperatively, the gain in uncorrected visual acuity (UCVA) ranged from 0.2 to 0.5 Log MAR in 10 eyes. Conclusion: Sutureless and glue free conjunctival autograft technique is easy, safe, effective, prevents potential adverse reactions encountered with the use of foreign materials. This technique has an acceptable pterygium recurrence rate that is comparable to conventional sutured conjunctival autograft for primary pterygium. Medicine Today 2018 Vol.31(1): 1-8